Chilean Political Documentary Video of the 1980s - Traverso, Antonio; Linero, G. (Palgrave Macmillan, 2014)
The chapter seeks to reconsider Chilean anti-dictatorship video documentary through both historical contextualization and close textual analysis of a series of landmark political video documentaries produced in Chile during that decade. The chapter proposes that these videos are significant components of Chile’s national screen culture’s ongoing engagement with the traumatic memory of the dictatorship period. The videos offer an example of oppositional media at a time when any form of opposition amounted to a defiant and risky gesture. These videos not only documented state violence and political resistance in Chile in the 1980s but constituted a form of resistance in their own right.